Does Gender Top Family Ties? Within-Couple and between-Sibling Sharing of Elderly Care - Matteo Luppi; Tiziana Nazio (European Sociological Review, 2019)
Most elderly care continues to be delivered informally within families. Yet we still lack a thorough understanding of how care responsibilities are shared across both family ties and generations. We explore the gender dimension of caregiving in the distribution of elderly care between couple members (care provided to parents and parents-in-law and to children or grandchildren) and its associations with siblings' sex composition in a range of European countries. Using SHARE data and multinomial multilevel models, we test how responsibility for elderly care is shared across children and mediated by their partners and their siblings' sex composition as well as how it is combined with other downward care responsibilities, towards children and grandchildren. Results confirm the very gendered nature of elderly care. But who do men shift elderly care responsibilities to? We find that elderly care is more likely shifted to sisters than brothers, especially when caregiving becomes intense. We also find that the lower contribution by sons does not seem to prompt transfers of care responsibilities to their female partners within couples. Finally, although upward and downward caring responsibilities might compete, we find that individuals who are more inclined to provide care tend to do so in both directions.
Keywords: 330